INTEGRATION OF SCIENCE AND PHILOLOGICAL EDUCATION. INTEGRATED APPROACH TO TEACHING UZBEK LANGUAGE IN TECHNICAL HIGHER EDUCATION - Shermatova Dilfuza Yakubjanovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article examines the focus on the teaching of the Uzbek language in technical higher education, the integration of language in the field of education and in the field of "Architecture and Construction". The use of modern educational technologies in strengthening the process of teaching the state language, student’s speech, love for the language, love for the motherland, respect for national and spiritual values ​​are promoted.